Analysis of the Rality of the Moral Climate and its Role in Reducing Organizational Silence: An Analytical Study of the Opinions of Heads of Academic Departments in a Sample of Private University Colleges in the City of Erbil/Kurdistan Region-Iraq - معروف جميل, بريشان; محمد حبيب, ديلان (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The research sought to diagnose the reality of the ethical climate in the universities under research and analyze the relationship and the impact of its dimensions (support, appreciation, independence, training and development, adaptability, and leadership), on the dimensions of organizational silence represented. By (submission, self-protection, social loyalty). The general framework of the research was to identify the problem by asking several questions about the reality of the organizational climate, the nature and impact of the relationship, and the reduction of organizational silence. A questionnaire was used to obtain the data. The research followed the descriptive analytical approach, where the main and sub-variables were described, as well as analyzing the relationships and influence between the variables, representing the research community in all private universities in the city of Erbil in the Kurdistan Region. Iraq has 9 universities. The sample represented (7) universities, and the number of respondents was (86), head of the scientific department. The two hypotheses were tested by a set of statistical tests using the computer program (SPSS V.23). The research reached a set of conclusions, the most important of which is the existence of high correlations and strong influences between the main and sub-variables at the macro and micro levels. The research suggested a set of proposals in light of the conclusions, including the necessity of harnessing the strong relationships between the two variables and their orientation towards serving the researched universities with the need to strengthen the relationship between each dimension of the ethical climate in the organizational limit. Silence.